Heart, mind, body: close interrelationships in cardiovascular disease. (2nd August 2020) - Richardson, Andy
Abstract : This month, Andy Richardson, BANCC Educational Advisor, writes about the benefits of practices involving mind–body concepts, such as yoga and tai chi.